(untitled) - Marshall, I. Howard (Michigan, U.S.A, 2004)
Applying scriptural insight to contemporary issues is one of the most important, yet most difficult, tasks that the church faces. The Bible, though written long ago, can speak authoritatively to contemporary ethical, doctrinal, and practical issues. Respected author I. Howard Marshall offers guidance for this perennial task in Beyond the Bible.
Keywords: Dogma, Development of